57.9k views
3 votes
Write the expression
sin(sin^-1 (√(3) / 2) - tan^-1 (x) as an algebraic expression involving no trigonometric functions. You don’t need to rationalize the denominator.

User Teri
by
5.7k points

1 Answer

4 votes

Answer:

Explanation:


let~sin ^(-1)(√(3) /2)=y\\sin y=√(3) /2=sin ~(\pi /3),sin (\pi -\pi /3)\\y=\pi /3,2 \pi /3


sin ^(-1)(√(3) /2)=\pi /3,2\pi /3

your question is not clear.

User CMArg
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.